STUDIES OF THE BIOSORPTION OF TEXTILE DYE ONTO WHEAT STRAW - YKHLEF LAIDANI; GHANIA HENINI; SALAH HANINI; AIDA FEKAOUNI (Scientific Study & Research: Chemistry & Chemical Engineering, Biotechnology, Food Industry)
The objective of this study is the valuation of a natural residue and its application for the removal of synthetic dye through the adsorption batch process. The determinations of the concentrations of dye have been performed using an UV–Vis spectrophotometer. The kinetics and thermodynamics of adsorption of Methylene blue by wheat straw were studied. Experimental data were analyzed by the Langmuir, Freundlich, and Temkin isotherms. The Langmuir isotherm showed that the maximum value of adsorption capacity was 85.47 mg∙g-1, and the coefficient of determination (R2) was 0.999. The experimental data fitted very well the pseudo-second-order kinetic model (R2= 0.998), also the intraparticle diffusion rate constants vary from 4.612 to 14.615 mg∙g-1∙min-1/2 for concentrations between 10 and 120 mg∙L-1, whereas diffusion is not the only rate-control step. The thermodynamic parameters were evaluated. The negative value of ΔH° (-13.850 kJ∙mol-1) indicated that the adsorption of Methylene blue on wheat straw was exothermic, the reaction was accompanied by a decrease in entropy (-0.255 J∙mol-1∙K-1). The Gibbs energy increased from -13.770 to -13.775 kJ∙mol-1. The studied system shows that the adsorption process is spontaneous.